2015
DOI: 10.1039/c4tb01964d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release kinetics from a surface modified microgel-based reservoir device

Abstract: A device constructed by sandwiching a thin film of poly(N-isopropylacrylamide)-co-acrylic acid (pNIPAmco-AAc) microgels between two thin layers of Au (all on a glass support) was used as a novel platform for controlled release of small molecules (drugs). In this submission, the model drug tris (4-(dimenthylamino) phenyl)methylium chloride (Crystal Violet, CV) was loaded into the microgel layer of the device by electrostatic interaction of its positive charge with the negative charges on the deprotonated AAc gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The Serpe group developed a novel microgel-based assembly (reservoir device) as a new platform for drug delivery. [112][113][114][115][116] The structure of this device and the release mechanism is shown in Fig. 10.…”
Section: Controlled Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The Serpe group developed a novel microgel-based assembly (reservoir device) as a new platform for drug delivery. [112][113][114][115][116] The structure of this device and the release mechanism is shown in Fig. 10.…”
Section: Controlled Drug Deliverymentioning
confidence: 99%
“…Furthermore, by modifying the top layer Au surface, we can control the drug release with a lower thickness of Au. 113 In another example, the release of small molecules can be controlled by the aggregation state of microgels. For example, by combining two oppositely charged microgels, we can control the microgels' aggregation behavior to control drug release.…”
Section: Controlled Drug Deliverymentioning
confidence: 99%
“…This is due to the ability of the microgels to absorb and bind small molecules (via electrostatics and other interactions), which can then be triggered to release via changes in environmental conditions . As reported previously, the ultrathin layer of Au deposited on the etalon devices via thermal evaporation deposition is porous, and the porosity can be easily tuned by changing the Au layer thickness , or via surface modification . Regardless of how the Au layer porosity is varied, it can be used to control the release rate of small molecules from the microgel layer of the etalons.…”
Section: Introductionmentioning
confidence: 94%
“…In the past few decades, stimuli-responsive polymers, also known as “smart” materials, have attracted much scientific interest because of their ability to respond to external stimuli, for example, changes in environmental conditions. Stimuli-responsive polymers have found numerous applications as self-healing materials, , stimuli-responsive actuators, , and drug delivery reservoirs. ,, The breadth of the application of stimuli-responsive polymers is a result of the diversity of their chemistry that allows them respond to specific chemical and/or physical stimuli, such as pH, , organic/inorganic molecules, , biomolecules, temperature, , light, , and electric field. , One of the most extensively studied stimuli-responsive polymers is poly­( N -isopropylacrylamide) (pNIPAm), which undergoes a transition from a water-soluble state to a relatively insoluble state when the temperature is increased above its lower critical solution temperature (LCST). , The LCST for pNIPAm in pure water is around 32 °C, above which the linear polymer chain shrinks from an extended (random coil) to collapsed (globule) state . pNIPAm can also be cross-linked into network structures to yield hydrogels or hydrogel particles (microgels or nanogels, depending on diameter); these cross-linked structures also exhibit an LCST where they undergo a transition from water swollen to deswollen .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also exhibit the potential of being utilized for the construction of biomedical apparatuses revealing enhanced and/or novel functions, as building blocks . In the design of controlled drug delivery systems, these many advantages make microgels the ideal candidates. Researchers have conducted numerous investigations to acquire unique microgel-based assemblies or reservoir devices as new platforms for drug distribution techniques. Gao et al described an experiment for devising a reservoir device as a unique platform for triggered and controlled micromolecule delivery, comprising pNIPAm- co -AAc microgel coating sandwiched among two thin coatings of gold. They reported that the microgel layer of the device was loaded with positively charged tris­(4-(dimethyl amino)­phenyl)­methylium chloride, which was released at a rate that might be regulated by the height of the gold coating covering the microgel, in a pH reliant fashion, and further validated that the model drug can be given-off in an “on–off” method, by methodically tuning the solution pH.…”
Section: Applications Of Stimuli-responsive Polymersmentioning
confidence: 99%